Comparing responses to critical realism - Austen, Siobhan; Jefferson, Therese (Routledge, 2006)
AbstractThis article is a study of the response of two heterodox schools of economic thought to 'new' philosophical ideas. Specifically, it considers the response within Post Keynesian and feminist economics to Tony Lawson's recent call for economists to pay greater attention to ontology and for economists to adopt research methods consistent with critical realism. Lawson's arguments were formally introduced to these schools over the space of a few years and continue to generate considerable discussion within their ranks. The focus of analysis in this article is on the debate about Lawson's ideas published in the leading journals associated with two schools of thought: The Journal of Post Keynesian Economics and Feminist Economics. The article contrasts the reception Lawson's ideas received in each of the two journals and suggests some reasons for these differences. It argues that some barriers to the adoption of new ideas exist in each school of thought and that this has implications for the direction and content of economic thought in heterodox schools.